Others' Pain Appraisals Modulate the Anticipation and Experience of Subsequent Pain. (1st July 2019) - Peng, Weiwei; Peng, Huini; Lu, Juanzhi; Fan, Bi; Cui, Fang
Abstract: The present study investigated how pain appraisals from other individuals modulated self-pain anticipation and perception. Appraisals of pain intensity from 10 other individuals were presented before the participants received identical electrical pain stimulation themselves. In reality, the presented other's pain appraisals, with either low or high in mean and variance, were generated by the experimenter, and were randomly paired with the subsequent electrical stimulation at either low or high intensity. Specifically, the mean and variance of others' pain appraisals were manipulated to induce participants' expectation and certainty to the upcoming pain. Subjective ratings of pain intensity and electroencephalographic (EEG) responses to the electrical stimulation, as well as anticipatory EEG activities measured prior to the onset of electrical stimulation, were compared. Results showed that the mean and variance of others' pain appraisal modulated the subjective pain ratings and the affective-motivational P2 responses elicited by the electrical stimulation, as well as anticipatory sensorimotor α-oscillation measured before the onset of pain stimulation. When the mean of others' pain appraisal was low, higher variance suppressed the sensorimotor α-oscillations and enhanced subsequent pain perception. In contrast, when the mean was high, the higher variance enhanced sensorimotor α-oscillations and suppressed subsequent pain perception. These results demonstrated that others' pain appraisals can modulate both of the anticipation and perception of first-hand pain. It also suggested that the top-down modulation of others' pain appraisals on pain perception could be partially driven by the different brain states during the anticipation stage, as captured by the prestimulus sensorimotor α-oscillations. Highlights: Others' pain appraisals modulated the first-hand pain anticipation and perception Mean and variance of others' appraisals modulated self-reported pain ratings Mean and variance of others' appraisals modulated pain elicited brain responses Others' appraisals influenced anticipatory stage captured by α-oscillations